2022
DOI: 10.3390/biotech11040054
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Antimalarial Drug Candidates Targeting Falcipain-2 Protein of Malaria Parasite—A Computational Strategy

Abstract: Falcipain-2 (FP-2) is one of the main haemoglobinase of P. falciparum which is an important molecular target for the treatment of malaria. In this study, we have screened alkaloids to identify potential inhibitors against FP-2 since alkaloids possess great potential as anti-malarial agents. A total of 340 alkaloids were considered for the study using a series of computational pipelines. Initially, pharmacokinetics and toxicity risk assessment parameters were applied to screen compounds. Subsequently, molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…To assess the mutagenicity of compounds, prediction of AMES toxicity was performed in this research. Hepatotoxicity testing was performed to determine a compounds hepatotoxicity, a compound was considered hepatotoxic if it interfered with the normal physiological function of the liver [26]. Furthermore, skin sensitization was performed to identify compounds that could cause an allergic reaction on the skin.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the mutagenicity of compounds, prediction of AMES toxicity was performed in this research. Hepatotoxicity testing was performed to determine a compounds hepatotoxicity, a compound was considered hepatotoxic if it interfered with the normal physiological function of the liver [26]. Furthermore, skin sensitization was performed to identify compounds that could cause an allergic reaction on the skin.…”
Section: Discussionmentioning
confidence: 99%
“…The figures 6d and 6e presented the plots of solvent assessable surface area (SASA) and HB, respectively within a suitable range of 490-538 nm 2 for ligand-Figure 5. BOILED egg model of hit compounds (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). BBB and GI permeability have been indicated by the yellow and colorless zones, respectively.…”
Section: Simulationsmentioning
confidence: 99%
“…The Biovia Discovery Studio 2021 was utilized to visualize and analyze docking interactions between proteins and ligands. [41] The 2-D structures of compounds (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) are provided in the supplementary material (Figures S1-S3).…”
Section: Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the study ndings and the differences in the morphological changes in parasites before and after Noscapine treatment (Fig 2 ), we could hypothesize the probable mechanism of action for Noscapine to act on the parasitized RBCs. In silico studies have recently demonstrated that in comparison to DHA, Noscapine could have better binding e cacy with the Falcipain-2(FP-2) protein, and therefore has the potential for blocking hemoglobin hydrolysis and parasite development (Nema et al 2022). Falcipain-2(FP-2) is the papain-like cysteine protease of P. falciparum localised in the food vacuole, and responsible for cleaving the membrane skeletal proteins during late parasite development.…”
Section: ; Rehman Et Al 2014)mentioning
confidence: 99%